Labor Rights and Dispute System Design: Assessing the Legal Legacy of the 2022 Qatar World Cup - Zachary R. Calo (German Law Journal, 2023)
The aim of this paper is not to relitigate Qatar’s human rights record but to assess the effectiveness of its labor reforms: the principal concern is dispute resolution and enforceability. While Qatar instituted a broad suite of labor law reforms in the years preceding the World Cup, questions remain about whether they have improved access to justice for migrant workers. More attention needs to be given to the dispute settlement system established by Law No. 13 of 2017 to assess if new legal norms translate into enforceable rights. It is argued that the labor dispute system has largely failed by not taking into account the circumstances that define the employer-employee relationship in Qatar, especially the stark imbalance in power. While reforms might endure at the level of formal law, the dispute system will fail to deliver genuine justice to workers unless it is refashioned.